Ultrastructural Study on the Antibacterial Activity of Artonin E versus Streptomycin against Staphylococcus aureus Strains - Zajmi, A.; Hashim, N.M.; Noordin, M.I.; Khalifa, S.A.M.; Ramli, F.; Ali, H.M.; El-Seedi, H.R. (Public Library of Science, 2015)
Staphylococci are facultative anaerobes, perfectly spherical un-encapsulated cocci, with a diameter not exceeding 1 micrometer in diameter. Staphylococcus aureus are generally harmless and remain confined to the skin unless they burrow deep into the body, causing life-threatening infections in bones, joints, bloodstream, heart valves and lungs. Among the 20 medically important staphylococci species, Staphylococcus aureus is one of the emerging human pathogens. Streptomycin had its highest potency against Staphylococcus infections despite the likelihood of getting a resistant type of staphylococcus strains. Methicillinresistant S. aureus (MRSA) is the persister type of Staphylococcus aureus and was evolved after decades of antibiotic misuse. Inadequate penetration of the antibiotic is one of the principal factors related to success/failure of the therapy. The active drug needs to reach the bacteria at concentrations necessary to kill or suppress the pathogen's growth. In turn the effectiveness of the treatment relied on the physical properties of Staphylococcus aureus. Thus understanding the cell integrity, shape and roughness is crucial to the overall influence of the therapeutic agent on S. aureus of different origins. Hence our experiments were designed to clarify ultrastructural changes of S. aureus treated with streptomycin (synthetic compound) in comparison to artonin E (natural compound). In addition to the standard in vitro microbial techniques, we used transmission electron microscopy to study the disrupted cell architecture under antibacterial regimen and we correlate this with scanning electron microscopy (SEM) to compare results of both techniques.